2017
DOI: 10.2174/1874285801711010023
|View full text |Cite
|
Sign up to set email alerts
|

ESBL Production Among E. coli and Klebsiella spp. Causing Urinary Tract Infection: A Hospital Based Study

Abstract: Introduction:Increase in extended-spectrum β-lactamases (ESBL) producing microbes in recent years has led to limitations of treatment options. This study aimed to assess the prevalence of ESBL producing E. coli and Klebsiella spp. at a tertiary hospital in Nepal.Methods:A total of 2209 non-repetitive mid-stream urine (MSU) samples were collected during the study period (March to September 2014). Identification of the isolates was done by Gram's staining followed by biochemical tests. Antibiotic susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
71
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 30 publications
37
71
7
Order By: Relevance
“…Maximum resistance was seen for Ampicillin, all 4-generations of . This susceptibility and resistance pattern is in accordance with other studies (Pooja Shakya et al, 2017;Akila et al, 2016 andDinesh Kumar, 2014 …”
Section: Resultssupporting
confidence: 93%
“…Maximum resistance was seen for Ampicillin, all 4-generations of . This susceptibility and resistance pattern is in accordance with other studies (Pooja Shakya et al, 2017;Akila et al, 2016 andDinesh Kumar, 2014 …”
Section: Resultssupporting
confidence: 93%
“…In present study, the prevalence of bacterial infection among study subjects is found to be 35.3%, in which Escherichia coli is the predominant organism and followed by Enterococcus faecalis and Klebsiella pneumoniae. AST showed that, out of total isolates, 53.2% were MDR.Similar finding was reported by Shakya et al,where 52.3% of the total isolates were MDR, in which the main pathogens are Escherichia coli 79.7%, Providencia species 5.1%,and Klebsiella pneumoniae 3.4% [4]. A study from eastern Nepal also showed that, 43.98 % of urine samples showed significant growth and pathogens were resistant to amoxycillin, co-trimoxazole, flouroquinolones and third-generation cephalosporins [12].…”
Section: Discussionsupporting
confidence: 85%
“…In Nepal the mortality rate is high due to diarrheal diseases, respiratory tract infection, blood stream infection, urinary tract infection, tuberculosis and sexually transmitted diseases [3]. The evidence of multidrug resistant pathogens is reported from the various studies conducted in different part of Nepal [4,5]. The major culprits include pathogens like extended-spectrum β-lactamaseproducing Escherichia coli and Klebsiella pneumonia, carbapenemresistant Enterobacteriaceae, Methicillin-Resistant Staphylococcus aureus (MRSA), Vancomycin Resistant Enterococcus (VRE), Pseudomonas aeruginosa and Acinetobacter baumannii.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted in 2012 in a tertiary care hospital of Sri Lanka, 13% of all community-acquired UTIs were due to ESBL producers. 21 The antibiotic sensitivity of the ESBL producers in the present study demonstrated relatively higher resistance rates against commonly used empirical antibiotics [ciprofloxacin (20.5%), norfloxacin (21.1%) and nalidixic acid (14.8%)] in the primary care setting. These findings suggest that empiric therapy with commonly used antibiotics is questionable in a background with an increased ESBL prevalence.…”
Section: Discussionmentioning
confidence: 48%